A Comprehensive Evaluation of Soil Fertility of Cultivated Land: A GIS-Based Soil Basic Niche-Fitness Model. Issue 5 (8th March 2016) - Nie, Yan; Yu, Jing; Peng, Yating; Wu, Yunga; Yu, Lei; Jiang, Yan; Zhou, Yong
ABSTRACT: This paper aimed at using the niche-fitness analysis method to assess soil fertility of cultivated land in Jianghan Plain in China. By introducing the niche-fitness theory into comprehensive analysis of soil fertility, an evaluation method was developed using geographic information systems (GIS) and the soil basic niche-fitness model (SBNFM). To begin with, 10 indicators were selected and used to assess the spatial differences of soil fertility for cultivated land, and its weight was decided using analytic hierarchy process (AHP). Soil samples were collected from topsoil (0–25 cm) in 58 units and examined for pH, organic matter (OM), total nitrogen (TN), etc. After standardizing soil attribute data of each unit, the optimum niche of every indicator was obtained and the soil basic niche-fitness value of each plot was calculated by using SBNFM. Finally, the soil fertility of the cultivated land was divided into four grades based on the shortest distance cluster analysis method in this area. Results indicate that the soil fertility of the cultivated land in this area was on the medium and high side, the percentages of area in grades 1, 2, 3 and 4 accounted for 33.43%, 35.99%, 22.70% and 7.88%, respectively; thus, approximately 70% of the cultivated land was classified in the top two grades. The linear-correlated relationship between niche-fitness value and rice yield has shown that SBNFM is an important and effective tool to analyze soil fertility and evaluate the quality of cultivated land. The above results might be helpful and support fertilizer management or agricultural activity in the study area.